A Reflection on Cahill's Interpretation of the Ethical and Cultural Point of Wittgenstein's Tractatus - Hossein Shaqaqi (Journal of Philosophical Investigations, 2022)
According to Wittgenstein's Tractatus Logico-Philosophicus, propositions of natural science are all meaningful propositions of language therefore there is no ethical proposition because alleged ones do not fulfil the criterion of meaningfulness of propositions, which is empirical verifiability. In addition, Wittgenstein somewhere considers Tractatus Logico-Philosophicus to have an important ethical point. There seems to be a conflict between Wittgenstein's recent claim, on the one hand, and the meaninglessness of ethics, on the other. In the face of this apparent conflict, we try to ponder the question of what is the ethical point of Tractatus Logico-Philosophicus. In answer to this question, we will pay attention to Kevin Cahill's interpretation of Wittgenstein. In Wittgenstein's view, modern culture prevents what he calls the experience of the wonder of the world. Cahill interprets the ethical point of Tractatus Logico-Philosophicus in connection with Wittgenstein's view on modern culture. What objection would Tractatus Logico-Philosophicus be subject to if Cahill's interpretation were correct? How defensible is the dependence of Cahill's interpretation of Tractatus on other Wittgenstein's works? At the end of our study, we will answer these questions.